2022
DOI: 10.47381/aijre.v29i2.221
|View full text |Cite
|
Sign up to set email alerts
|

Equal or Equitable? The Role of Flexibility Within Online Education

Abstract: Online study is generally associated with the terms flexible and flexibility. Many students choose to study online specifically for the flexibility that is offered, hoping they can combine their studies with multiple other responsibilities in their lives. For students living in regional and rural areas, such flexibility can be even more important, given the additional difficulties they face in accessing campus facilities. While a flexible learning environment has the potential to contribute positively towards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 18 publications
1
5
0
1
Order By: Relevance
“…It is likely that these bad experiences have been jointly shaped by the pandemic, the rushed transition it forced towards online teaching methods, and the socio-emotional effects it had on educators more generally. This conjecture is further supported by prior scholarly evidence that points towards the many benefits of online education at large (Dyment et al, 2020 ; Huang, 1997 ; Mayadas et al, 2009 ; Muir et al, 2019 ; Stone, 2021 ; Stone et al, 2019 ; Summers et al, 2023 ). Therefore, as online teaching methods become more prominent in higher educational institutions, it is important to disentangle the role of the pandemic in shaping educators’ teaching experiences.…”
Section: Introductionsupporting
confidence: 54%
“…It is likely that these bad experiences have been jointly shaped by the pandemic, the rushed transition it forced towards online teaching methods, and the socio-emotional effects it had on educators more generally. This conjecture is further supported by prior scholarly evidence that points towards the many benefits of online education at large (Dyment et al, 2020 ; Huang, 1997 ; Mayadas et al, 2009 ; Muir et al, 2019 ; Stone, 2021 ; Stone et al, 2019 ; Summers et al, 2023 ). Therefore, as online teaching methods become more prominent in higher educational institutions, it is important to disentangle the role of the pandemic in shaping educators’ teaching experiences.…”
Section: Introductionsupporting
confidence: 54%
“…Students come to online courses with diverse needs and preferences, and appreciate the flexibility of studying online, enabling them to schedule study around work and family commitments (Bettinger & Loeb, 2017). However, it is vital that institutions that deliver online learning also deliver on these expectations, particularly given the visible marketing of online learning as flexible (Stone et al., 2019). In keeping with wider research (Burke, 2021), our students demonstrated a range of preferences for interpersonal engagement, with some desiring connection and interaction and others preferring to complete studies privately.…”
Section: Discussion and Implications For Practicementioning
confidence: 99%
“…The building in of greater differentiation of engaging with the learning materials and completing assessment tasks, and ways of connecting with staff and peers, is visibly desired. This will require not only flexibility on behalf of those who facilitate online arts courses, but more broadly, flexibility within institutions where rigid regulations may work against the delivery of such flexibility (Stone et al., 2019).…”
Section: Discussion and Implications For Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Esta forma particular de trabajo se caracteriza por una gran flexibilidad y mayor autonomía, así como también un mayor sentido de aislamiento de los compañeros de trabajo y una menor supervisión de lo realizado (Robbins y Judge, 2009). Dentro de los ámbitos en los que la masificación del teletrabajo ha influido se encuentra la educación (Stone et al, 2019). Al respecto, la realidad moldeada netamente a partir de las tecnologías de la información ha traído consigo tanto ventajas como desventajas.…”
Section: Introductionunclassified